1,25-Dihydroxyvitamin D3 attenuates IL-1β secretion by suppressing NLRP1 inflammasome activation by upregulating the NRF2-HO-1 pathway in epidermal keratinocytes - Takahisa Nakajo (Elsevier, 2021)
The nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing protein (NLRP) inflammasome is a key inflammatory signaling pathway activated via a two-step signaling process consisting of priming and activation steps. Several studies have shown that 1,25-dihydroxyvitamin D3 (1,25(OH)2VD3) inhibits the priming step required for NLRP3 inflammasome activation in immune cells. However, as activating the NLRP1 inflammasome in keratinocytes does not necessarily require a priming step, whether 1,25(OH)2VD3 inhibits NLRP1 activation in unprimed keratinocytes is currently unknown. In this study, we showed that 1,25(OH)2VD3 inhibits nigericin-induced NLRP1 inflammasome activation in unprimed keratinocytes. 1,25(OH)2VD3 suppressed nigericin-induced interleukin-1β (IL-1β) secretion and caspase-1 activation in human primary keratinocytes. In addition, 1,25(OH)2VD3 significantly inhibited the formation of apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) oligomers and specks, but not caspase-1 enzymatic activity, suggesting that 1,25(OH)2VD3 prevents NLRP1-ASC complex assembly in keratinocytes. Vitamin D receptor (VDR)-knockdown abolished the inhibitory effects of 1,25(OH)2VD3 on nigericin-induced ASC oligomerization and IL-1β secretion, suggesting that 1,25(OH)2VD3 suppresses inflammasome activation via VDR signaling. Furthermore, nigericin induced K+ efflux and cellular reactive oxygen species (ROS) production, and 1,25(OH)2VD3 pretreatment suppressed nigericin-induced ROS production. 1,25(OH)2VD3 increased the expression of both nuclear factor erythroid 2-related factor 2 (NRF2) and heme oxygenase-1 (HO-1), whereas HO-1 inhibition or NRF2 and HO-1 knockdown abrogated the inhibitory effects of 1,25(OH)2VD3 on IL-1β secretion. Our results indicate that 1,25(OH)2VD3 inhibits nigericin-induced activation step of NLRP1 inflammasome activation in unprimed keratinocytes. Our findings reveal the mechanism underlying the inhibitory effect of 1,25(OH)2VD3, which involves NRF2-HO-1 pathway activation through the VDR, providing further insight into the potential function of 1,25(OH)2VD3 as a therapeutic agent for inflammasome-related skin diseases.